Are Pain Screening and Functional Assessment Results Associated with New Diagnoses and Treatment for Pain in Primary Care? An Observational Study - Hudson Scholle S; Nguyen-Louie TT; Bifulco L; Blaz JW; Blankson ML; Channamsetty V; Anderson DR (Journal of Pain Research, 2022)
Sarah Hudson Scholle,1 Tam T Nguyen-Louie,1 Lauren Bifulco,2 Jacquelyn W Blaz,1 Mary L Blankson,2 Veena Channamsetty,2 Daren R Anderson2 1National Committee for Quality Assurance, Washington, DC, USA; 2Weitzman Institute, Community Health Center, Inc., Middletown, CT, USACorrespondence: Sarah Hudson Scholle, National Committee for Quality Assurance (NCQA), 1100 13th St. NW, Third Floor, Washington, DC, 20005, USA, Tel +1-202-955-1726, Fax +1-202-955-3500, Email scholle@ncqa.orgPurpose: To determine if pain screening and functional assessment results are associated with new diagnoses and treatment for pain in primary care.Patients and Methods: Observational study at 13 primary care sites of a statewide federally qualified health center that implemented routine screening and functional assessment for all adults in primary care. The study group included 10,091 adults aged 18+ who had an in-person visit between July 2, 2018, and June 1, 2019, where they screened positive for chronic pain and completed a 3-question functional assessment with the PEG (Pain, Enjoyment of Life, General Activity). Multivariate logistic regressions quantified associations between pain frequency, diagnosis and treatment, sociodemographics, comorbidities, and self-reported severe pain impairment with pain diagnoses and treatment documented after screening.Results: Patients were mostly women (60.3%), Latinx (41.1%), English-speaking (80.1%), and Medicaid-insured (62.0%); they averaged 49.1 years old (SD = 13.7 years). Patients with severe pain impairment or who were Latinx were more likely to get a newly documented pain diagnosis (absolute risk difference [ARD]: 13.2% and 8.6%, ps < 0.0001), while patients with mental health/substance use or medical comorbidities were less likely (ARDs: − 20.0% to − 6.2%, ps < 0.001). Factors most consistently associated with treatment were prior treatment of the same modality (4 of 7 treatments, ARDs = 27.3% to 44.1%, ps < 0.0001), new pain diagnosis (5 of 7, ARDs = 3.2% to 27.4%, ps < 0.001), and severe impairment (4 of 7, ARDs = 2.6% to 6.5%, ps < 0.0001). A new diagnosis had the strongest association with non-opioid pain analgesics and physical medicine (ARD = 27.0% and 27.4%, p < 0.0001). Latinx patients were less likely to receive opioid analgesics and mental health/substance use medications and counseling (ARDs = − 3.3% to 7.5%, ps < 0.0001).Conclusion: Screening and assessment with patient-reported tools may influence pain care. Care for Latinx patients differed from non-Latinx white patients.Keywords: PEG, chronic pain, primary care, patient-reported outcome measures, federally qualified health center, equity